2022
DOI: 10.1021/acs.langmuir.2c00301
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics and Surface Interactions of Nickelocene Adsorbed on Silica: A Paramagnetic Solid-State NMR Study

Abstract: When grinding nickelocene with silica in the absence of a solvent at room temperature, it adsorbs on the surface within the pores. This has also been demonstrated visually by adsorbing green nickelocene in the pores of a large colorless silica gel specimen. While this dry adsorption and translational mobility of nickelocene within the pores is proven visually, the site-to-site mobility of the nickelocene molecules and their orientation toward the surface are not yet understood. In this contribution, mesoporous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…From a practical perspective, it easily packs into a solid-state NMR rotor and due to its large average particle diameters (0.062-0.2 mm) it can be handled in a glove-box or at the Schlenk line under an inert gas stream without dust issues. The adsorption results obtained with a silica surface for metallocenes [7][8][9][10] and phosphine oxides 11,12 translate to other surfaces such as alumina or activated carbon, as demonstrated in the case of ferrocene adsorbed on activated carbon 13,14 and triphenylphosphine oxide adsorbed on alumina. 15 We and others have previously shown that diverse species with high melting points can be adsorbed on solid supports in the absence of solvents.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…From a practical perspective, it easily packs into a solid-state NMR rotor and due to its large average particle diameters (0.062-0.2 mm) it can be handled in a glove-box or at the Schlenk line under an inert gas stream without dust issues. The adsorption results obtained with a silica surface for metallocenes [7][8][9][10] and phosphine oxides 11,12 translate to other surfaces such as alumina or activated carbon, as demonstrated in the case of ferrocene adsorbed on activated carbon 13,14 and triphenylphosphine oxide adsorbed on alumina. 15 We and others have previously shown that diverse species with high melting points can be adsorbed on solid supports in the absence of solvents.…”
Section: Introductionmentioning
confidence: 76%
“…15 We and others have previously shown that diverse species with high melting points can be adsorbed on solid supports in the absence of solvents. For example, solid metallocenes, [7][8][9][10] phosphine oxides, 11,12,15 and polycyclic aromatic hydrocarbons (PAH) 16 including their chromium tricarbonyl complexes, 17 can be adsorbed on a variety of surfaces by grinding the dry components with a mortar and pestle or just bringing the solid components into contact. 8,10 The nucleus 31 P is ideal to probe the dynamics and structures of surface-bound species containing phosphorus 11,12,15,18 by solid-state NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate whether the distribution of molecules of 1 and 2 is homogeneous throughout the crystal lattice and a genuine solid solution forms, solid-state NMR spectroscopy has been applied. ,− , As mentioned above, while 1 is diamagnetic, 2 is paramagnetic, featuring two unpaired electrons. The latter have an impact on the solid-state NMR spectra; however, paramagnetic NMR spectroscopy of solids is well established. ,,,− ,, In the case of a solid solution with random distribution of 1 and 2 in the crystal, the paramagnetism of 2 should influence the 1 H NMR signal characteristics of 1 . For diamagnetic compounds and materials, besides the residual linewidth (half-width of the isotropic line when the sample is rotated), the chemical shift anisotropy (CSA, overall shape of the signal including the rotational sidebands) , is a relevant characteristic of a functional group or material.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, co-crystallization or the formation of solid solutions of crystalline metallocenes has not been described in the literature yet, although such well-defined materials would have great potential as precursors for creating heterobimetallic nanoparticles and dual-atom catalysts . In particular, ferrocene and nickelocene are interesting targets for co-crystallization because they prefer the same space group P 2 1 / n for their single crystals and have practically the same size and shape. , Earlier, we have studied ferrocene and nickelocene, adsorbed together on a silica surface, and found that they mix on the molecular level . This mixing is easily explained by the dynamics and especially the translational mobility of both metallocenes on the surface. As a next step, we sought to investigate mixtures of pure ferrocene and nickelocene regarding their potential to form randomly mixed crystals with homogeneous distribution of the components in the crystal lattice, i.e., crystalline solid solutions of the metallocenes.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous silica, such as MCM-41 and SBA-15, has attracted considerable interest for application as an adsorbent material for removal of environmental pollutants such as volatile organic compounds . Its specific surface area of larger than 500 cm 2 g –1 is a prerequisite for excellent molecular adsorption due to the increased number of adsorption sites. , The size of the mesopore is of significance to enhance the adsorption performance because adsorbents require open spaces sufficiently large to accommodate guest molecules. , In addition to the textural properties of mesopores, the functionalization of mesopore surfaces, such as condensation of Si–OH groups and organic surface modification, is decisive for the confinement of guest molecules. The functionalization of porous silica materials is mainly performed by two approaches: post-synthesis grafting and direct co-condensation with functionalized precursors. The post-synthesis grafting can be used to integrate various functional groups to the mesopore surfaces, whereas organosilane and silica precursors are condensed together in direct co-condensation enabling a uniform distribution of functional groups …”
Section: Introductionmentioning
confidence: 99%